DETERMINATION OF INFLUENCE AND DIFFERENCES OF ANTHROPOMETRIC CHARACTERISTICS AND MOTOR SKILLS IN TWO GENERATION STUDENTS IN THE ATHLETIC DISCIPLINE – SPRINT 100m. - Simeonov, Aleksandar; Ratko Pavlović (My University, 2021)
Anthropometric characteristics, motor skills as well as good technical performance are very important in the result of the athletic discipline – sprint 100m. The aim of this research was to determine the impact and differences in morphological characteristics and motor skills in athletic discipline sprint 100m., at both generations of students at the Faculty of Physical Education, Sports and Health. The research has been done on a sample of 100 respondents, consisted of full-time second year students at the age of 20 years with ± of 6 months at the Faculty of Physical Education Sport and Health in Skopje, divided into two groups of 50 respondents in both generations surveyed - 2015 and 2017.. Methods: In our research for assessment of the morphological structure of the respondents, 12 morphological variables were used and 5 motor variables for assessment of psychomotor abilities. The athletic discipline – sprint 100m is used as a criterion variable. Results: From the obtained results of the regression analysis, we noticed that the morphological variables have a significant impact on the criterion variable – sprint 100m in both groups of participants - 2015 generation (Q=.004) and generation 2017 (Q=.002). Regarding the motor skills that were the subject of analysis in our research, we found that all five motor variables used as a test for their abilities have a significant impact as a system on the criterion variable – sprint 100m (Q=.000). According to the multivariate (MANOVA) and univariate analysis (ANOVA) of the results of both groups of entities, we noticed that both groups of respondents differ in their morphological characteristics and biomotor abilities (Q=.000). Conclusion: Based on the results obtained from the applied research procedure, we came to the conclusion that the morphological structure of the respondents has a significant role in achieving greater height in аthletic discipline – sprint 100m. In terms of motor skills, we came to the conclusion that students should use the motor tests that were used in the research in the preparation phase, in order to be able to successfully meet the norm and achieve better results in the discipline – shot put. The differences between the respondents would be smaller if they pay more attention to the preparation for the fulfillment of the norm in this athletic discipline.
Keywords: morphology, motor skills, sprint 100m., analysis, impact, differences